Raising children emerging needs, modern risks, and social responses - Berrick, Jill Duerr; Gilbert, Neil, 1940- (Oxford : Oxford University Press, 2008)
Modern family life raises tough questions: Who should be responsible for children's daily care? How can their financial support be fairly allocated between parents? Should extended family members be paid for their help? Can women have full careers and also be good mothers? 'Raising Children' takes on these questions and more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child rearing -- United States; Parenting -- United States